2021
DOI: 10.1002/for.2767
|View full text |Cite
|
Sign up to set email alerts
|

Cointegration, information transmission, and the lead‐lag effect between industry portfolios and the stock market

Abstract: This paper shows that lagged information transmission between industry portfolio and market prices entails cointegration. We analyze monthly industry portfolios in the US market for the period 1963-2015. We find cointegration between six industry portfolio and market prices. We show that the equilibrium error, the long-term common factor between industry portfolio and market cumulative returns, has strong predictive power for excess industry portfolio returns. In line with gradual information diffusion across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Nevertheless, the financial shocks lag with the actual side of the economy because of the information transmission. As Troster et al [62] point out in their study, industry information has a predictive effect on the financial returns in the stock market. The observations during the COVID-19 period show that the lags between SCHI and the US indexes exhibit a reverse relationship compared to the previous periods as the yield volatility in China matches the same day US indexes, indicating an increasing impact power of China during the pandemic and a mimic effect of the US stock market to China's one.…”
Section: Datamentioning
confidence: 93%
“…Nevertheless, the financial shocks lag with the actual side of the economy because of the information transmission. As Troster et al [62] point out in their study, industry information has a predictive effect on the financial returns in the stock market. The observations during the COVID-19 period show that the lags between SCHI and the US indexes exhibit a reverse relationship compared to the previous periods as the yield volatility in China matches the same day US indexes, indicating an increasing impact power of China during the pandemic and a mimic effect of the US stock market to China's one.…”
Section: Datamentioning
confidence: 93%
“…Most notably, Kanas and Kouretas ( 2005 ) showed an improvement in the forecasting ability of cointegration between the lagged price of large-firm portfolios and the current price of small-firm portfolios in the UK equity market. Troster et al ( 2021 ) found that the long-term common factor (equilibrium error) between industry portfolios and market cumulative returns has strong predictive power for monthly excess industry portfolio returns in the US. Hence, considering long-run relationships may improve the forecasting ability of international industry returns.…”
Section: Introductionmentioning
confidence: 99%